2019
DOI: 10.1016/j.ijmedinf.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking retrospective think-aloud as a novel approach for a usability evaluation

Abstract: Objective: To report on the use of an eye-tracking retrospective think-aloud for usability evaluation and to describe its application in assessing the usability of a mobile health app. Materials and Methods: We used an eye-tracking retrospective think-aloud to evaluate the usability of a HIV prevention mobile app among 20 young men (15–18 years) in New York City, NY; Birmingham, AL; and Chicago, IL. Task performance metrics, critical errors, a task completion rate per participant and a task completion rate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 33 publications
(48 reference statements)
1
26
0
2
Order By: Relevance
“…Cho et al, [16] demonstrated an improvement on usual eye-tracking protocols by devising a retrospective think-aloud, and related findings from eye tracking measures to success of failure in task completion. The new method asked participants to share their inner experience using the app and explain their experience and gaze patterns during errors making it possible to catch instances in which the user had more confidence than warranted, i.e., problems that would be undetected in traditional usability testing.…”
Section: Discussionmentioning
confidence: 97%
“…Cho et al, [16] demonstrated an improvement on usual eye-tracking protocols by devising a retrospective think-aloud, and related findings from eye tracking measures to success of failure in task completion. The new method asked participants to share their inner experience using the app and explain their experience and gaze patterns during errors making it possible to catch instances in which the user had more confidence than warranted, i.e., problems that would be undetected in traditional usability testing.…”
Section: Discussionmentioning
confidence: 97%
“…For example, several studies have used eye-tracking techniques to examine how users interact with the web interface and put forward some suggestions for improving the interface design (Kules & Xie, 2011;Harris, Sillence, & Briggs, 2009). Besides, some researchers (Koybasi & Cagiltay, 2012;Cho et al, 2019;Schaarup et al, 2015) have used eye-tracking technology to evaluate the usability of online system, which increased the accuracy and completeness in the usability tests. However, in a systematic review, Maramba et al (2019) have identified, explored, and summarized the methods used in the usability testing of eHealth applications, and suggested that automated methods such as eye tracking have not gained traction in evaluating health apps.…”
Section: Application Of Eye-tracking Technology In the Quality Evaluamentioning
confidence: 99%
“…A general attention model based on eye gaze was proposed. The use of an eye-tracking retrospective think-aloud for usability evaluation and description of this application in assessing the usability of a mobile health app is assessed in Reference [35]. The authors used an eye-tracking retrospective think-aloud to evaluate the usability of an HIV prevention mobile app among 20 young men (15-18 years) in New York City, NY; Birmingham, AL; and Chicago, IL.…”
Section: Related Workmentioning
confidence: 99%